Understanding social integration and health outcomes among China's internal migrants: a systematic review - Yang, Xiao; Li, Yuxuan; Tang, Kun (Frontiers in Public Health, 2025)
BackgroundThe internal migrant populations in China have contributed significantly to the country's social and economic landscape, yet health disparities among migrants remain a pressing concern. Social integration is considered a critical factor influencing health outcomes, but evidence on this relationship is fragmented. This systematic review aims to synthesize existing studies to explore the association between social integration and health outcomes, including healthcare service utilization, self-reported health (SRH), and non-communicable disease (NCD), among internal migrants in China.MethodsA systematic search was conducted across three databases (PubMed, EMBASE, PsycINFO) to identify studies published from January 2014 to November 2024 according to the protocol (INPLASY2024110085). The JBI assessment tool was used to assess the quality of the included studies.ResultsA total of 16 eligible cross-sectional studies were identified, focusing on the multidimensional aspects of social integration, including economic integration, acculturation, social networks and self-identity and their influence on health outcomes. Eleven papers focused on health service utilization, four concentrated on SRH and one discussed both NCDs and SRH. The majority of included studies indicated a significantly positive association between social integration and health outcomes of internal migrants.ConclusionSocial integration plays a crucial role in addressing health disparities among internal migrants in China. This review emphasizes the need for initiatives at all levels to enhance economic inclusion, cultural adaptation, and social networks to foster better social integration for the migrant community. Addressing these gaps will promote equitable healthcare access and improve the wellbeing of internal migrants in China.Systematic review registrationIdentifier INPLASY2024110085, https://inplasy.com/inplasy-2024-11-0085/.